Managing innovation performance: Results from an industry-spanning explorative study on R&D key measures - Peter M. Bican; Alexander Brem (Creativity and Innovation Management, 2020)
Research on R&D performance measures applied in firms is still scarce. Based on the established “R&D laboratory as a system” thinking, systematically derive and identify R&D department level key performance measures. Through a mixed-method approach, grounded in (1) literature and (2) text analysis, 154 R&D performance measures were developed. Amongst those, an (3) online expert survey, as well as (4) three independent focus group workshops with >40 industry experts from more than ten industries identified and validated ten key R&D performance measures. All industry experts involved are members of an innovation network, additionally accounting for innovation network effects. In contrast to earlier research, some of the measures like degree of anticipation of internal customer needs were perceived both by the survey respondents and the focus groups as key measures, indicating that behavioral measures should not be excluded per se. However, the importance of external validity of R&D performance or indicators to measure performance in relation to activities outside the R&D department were not confirmed. Hence, we partly confirm the relevance of the original “R&D Lab” measures, contributing a more granular level, thereby drawing implications for future research and practice.
Keywords: 330; innovation management; KPI; performance indicators; performance measurement; R&D management; R&D performance; innovation measures